Diversity of Empruthotrema Johnston and Tiegs, 1992 parasitizing batoids (Chondrichthyes: Rajiformes and Myliobatiformes) from the Southwest Atlantic Ocean, with description of three new species - Irigoitia, Manuel Marcial; Braicovich, Paola Elizabeth; Rossin, María A.; Canel, Delfina; Levy, Eugenia; Farber, Marisa Diana; Timi, Juan Tomás (Springer, 2020)
During an extensive research project involving 519 specimens of batoids, including 13 species of Rajiformes and Myliobatiformes (Chondrichthyes) from the Argentine Sea, three new species of Empruthotrema were found and are described using morphologic characteristics and two molecular markers: LSU rDNA and COI mtDNA. The new species can be distinguished from their congeners by the number and distribution of the marginal loculi, the length and morphology of male copulatory organ, and the presence of eyespots. Additionally, multivariate analysis identified the dimensions of the pharynx and ejaculatory bulb as diagnostic features. Host specificity and previous records of the genus in the region are discussed. This is the first description of new species in this genus for the Southwestern Atlantic Ocean, as well as for arhynchobatid hosts.